Acute pyomyositis of the adductor magnus muscle involving the posterior and lateral thigh compartments: a case report of diagnosis and management - Rajesh Bawale; Jay Watson; Karshe Yusuf; Dilip Pillai; Bijayendra Singh (Journal of Trauma and Injury)
Bacterial infection of skeletal muscle can lead to the formation of abscesses. Primary pyomyositis is typically seen in tropical countries, and Staphylococcus aureus is the commonest causative organism. We present a case of acute adductor magnus muscle abscess (pyomyositis) with spread to adjacent thigh compartments via the perforators without iliopsoas muscle involvement. Due to the involvement of the entire thigh compartment, systemic antibiotic treatment alone was insufficient, whereas surgical drainage improved the clinical picture. The aetiological organism was S. aureus. Herein, we report the case of a patient who had primary pyomyositis, rather than a secondary type, that spread to the posterior and lateral aspect of the thigh through the second and third perforators, which pierce the adductor magnus muscle belly before entering the femur.